Molecular Modeling and Spectroscopic Studies of Benzothiazole - V. Sathyanarayanmoorthi; R. Karunathan; V. Kannappan (Journal of Chemistry)
The Fourier Transform (FT) infrared and FT-Raman spectra of benzothiazole (BT) have been recorded and analyzed. The equilibrium geometry, bonding features, and harmonic vibrational frequencies have been investigated by ab initio and density functional theory (DFT) methods. The assignments of the vibrational spectra have been carried out. The computed optimized geometric bond lengths and bond angles show good agreement with experimental data of the title compound. The calculated HOMO and LUMO energies indicate that charge transfer occurs within the molecule. Stability of the molecule due to conjugative interactions arising from charge delocalization has been analyzed using natural bond orbital (NBO) analysis. The results show that the electron density (ED) in the and antibonding orbital and second-order delocalization energies confirm the occurrence of intramolecular charge transfer (ICT). The calculated results were applied to simulate infrared and Raman spectra BT which show good agreement with recorded spectra.